ANALYSIS OF MEANINGFULNESS OF CROSS-CORRELATION CONNECTIONS BETWEEN MORPHOMETRIC INDEXES OF MAJOR SALIVARY GLANDS OF RATS AFTER STIMULATION - Єрошенко, Г.А. (World of Medicine and Biology, 2012)
The purpose of work was determination of meaningfulness of cross-correlation connections between separate strong morphometric indexes of parotid and sabmandibular salivary glands of rats in a norm and after introduction of adrenalin and acetylcholinum. For determination of presence of really existent connection between metrical indexes determined meaningfulness of coefficients of correlation for establishing connections between certain morphometric parameters - external diameter, by the diameter of lumen and high of epitheliocytes of end-pieces and ducts by the diameters of capillaries, post-capillaries and venules. The by us metrical and statistical finding testify to different influence of adrino- and cholinomimetics on a secretory process in end-pieces and ductal system of parotid and sabmandibular salivary glands. By basic criteria which represent the changes of the functional state of parotid glands it is necessary to count the external diameters of secretory components of lobules and diameters of capillaries. By basic metrical criteria which represent the functional state of sabmandibular gland there is a value of external diameter and diameter of lumen of ephithelial secretory components.